Cytomegalovirus viremia in lung transplantation during and after prophylaxis. Issue 3 (22nd March 2019) - Chang, Andrew; Musk, Michael; Lavender, Melanie; Wrobel, Jeremy; Yaw, Meow‐Chong; Lawrence, Sharon; Chirayath, Shiji; Boan, Peter
Abstract: Background: Lung transplantation has a high risk of cytomegalovirus (CMV) viremia and disease. Methods: Valganciclovir was planned for 6 months in CMV recipient seropositive (R+) lung transplants (LTs) and given long‐term in D+R− LTs. CMV viremia was monitored regularly during and after prophylaxis in all patients. Results: Of 137 LTs, 22 were D+R−, 49 D+R+, 43 D−R+, and 23 D−R−, with median follow up 4.1 years (IQR 2.1‐6.2 years). CMV viremia at any time occurred in 44.5% of LTs. CMV viral load >10 3  c/mL was uncommon (9/77 episodes). CMV viremia occurred at median 665 days (IQR 271‐1411 days), in 5.1% LTs <6 months, 20.3% LTs 6‐12 months, and 35.8% LTs >12 months. CMV disease occurred in 6 (4.4%) LTs at an overall rate of 1.0 episode per 100 person‐years: two of these cases were organ‐specific disease, four were CMV syndrome. One case of ganciclovir‐resistant CMV was diagnosed. D+R+ and D+R− LTs had higher viremia rates than the D−R+ group. No viremia occurred in D−R− LTs. CMV viremia was not associated with age, gender, type of LT, indication for LT, acute rejection, bronchiolitis obliterans syndrome, or mortality. Conclusions: Prophylaxis for 6 months in D+R+ and D−R+, and past 12 months in D+R− LTs, with long‐term monitoring in all patients using a sensitive assay, and reinstitution of valganciclovir for low‐level viremia was effective at markedly reducing the incidence of CMV disease. CMV D−R− LTs do not need routine CMV monitoring.